2009
DOI: 10.1002/ijc.24950
|View full text |Cite
|
Sign up to set email alerts
|

RNAi‐mediated MEK1 knock‐down prevents ERK1/2 activation and abolishes human hepatocarcinoma growth in vitro and in vivo

Abstract: The mitogen-activated protein kinases MEK/ERK pathway regulates fundamental processes in malignant cells and represents an attractive target in the development of new cancer treatments especially for human hepatocarcinoma highly resistant to chemotherapy. Although gene extinction experiments have suggested distinct roles for these proteins, the MEK/ERK cascade remains widely considered as exhibiting an overlap of functions. To investigate the functionality of each kinase in tumorigenesis, we have generated sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
(64 reference statements)
4
24
0
Order By: Relevance
“…ERK is a pivotal downstream effecter of MEK, as RNAi-mediated MEK knockdown prevents ERK activation and abolishes hepatocarcinoma growth [22]. However, in this study, we found MEK1 regulates YAP via an ERK independent manner; because ectopic expression of ERK has no effects on YAP (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…ERK is a pivotal downstream effecter of MEK, as RNAi-mediated MEK knockdown prevents ERK activation and abolishes hepatocarcinoma growth [22]. However, in this study, we found MEK1 regulates YAP via an ERK independent manner; because ectopic expression of ERK has no effects on YAP (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The ERK signaling pathway can be activated in response to a diverse range of extracellular stimuli, including mitogens, growth factors, and cytokines, as well as immediate extracellular stresses, such as radiation or chemotherapeutic agents (53)(54)(55). We previously demonstrated that treatment with 30 M tetrandrine for 24 h repressed ERK activation and led to apoptosis in cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…They are mostly associated with the mitogen-activated protein kinase (MAPK) pathway (9). Constitutively activated extracellular signal-regulated kinases (ERK) have been shown to increase proliferation of human HCC cells (10). So far there is no report that investigates the effects of Baicalein on ERK in HCC.…”
Section: Preferential Inhibition Of Hepatocellular Carcinoma By the Fmentioning
confidence: 99%